A Case for Aid : Building a Consensus for Development Assistance. - Wolfensohn, James D. (World Bank e-Library., 2002)
Annotation "This publication includes readings related to the U.N. International Conference on Financing for Development, held in Monterrey, Mexico, in March 2002:(a) 'A Partnership for Development and Peace, ' a keynote speech given by World Bank president James D. Wolfensohn, two weeks before the Monterrey event;(b) 'Making the Case for Aid, ' a note by World Bank chief economist Nicholas Stern, discussing the consensus that emerged from Monterrey;(c) 'The Role and Effectiveness of Development Assistance, ' a report presented at Monterrey, detailing lessons from the World Bank's experience, written by Ian Goldin, Halsey Rogers, and Nicholas Stern;(d) 'The Monterrey Consensus, ' the official United Nations document outlining the major agreements reached at the conference, with an introduction by Mats Karlsson, World Bank vice president for external and U.N. affairs."